A novel force transduction pathway from a tension sensor to the gate in the mechano-gating of MscL channel - Sawada, Yasuyuki; Nomura, Takeshi; Martinac, Boris; Sokabe, Masahiro (Frontiers in Chemistry, 2023)
The bacterial mechanosensitive channel of large conductance MscL is activated exclusively by increased tension in the membrane bilayer. Despite many proposed models for MscL opening, its precise mechano-gating mechanism, particularly how the received force at the tension sensor transmits to the gate remains incomplete. Previous studies have shown that along with amphipathic N-terminus located near the cytoplasmic surface of the membrane, Phe78 residue near the outer surface also acts as a “tension sensor,” while Gly22 is a central constituent of the “hydrophobic gate.” Present study focused on elucidating the force transmission mechanism from the sensor Phe78 in the outer transmembrane helix (TM2) to the gate in the inner transmembrane helix (TM1) of MscL by applying the patch clamp and molecular dynamics (MD) simulations to the wild type MscL channel and its single mutants at the sensor (F78N), the gate (G22N) and their combination (G22N/F78N) double mutant. F78N MscL resulted in a severe loss-of-function, while G22N MscL caused a gain-of-function channel exhibiting spontaneous openings at the resting membrane tension. We initially speculated that the spontaneous opening in G22N mutant might occur without tension acting on Phe78 residue. To test this hypothesis, we examined the (G22N/F78N) double mutant, which unexpectedly exhibited neither spontaneous activity nor activity by a relatively high membrane tension. To understand the underlying mechanism, we conducted MD simulations and analyzed the force transduction pathway. Results showed that the mutation at the tension sensor (F78N) in TM2 caused decreased interaction of this residue not only with lipids, but also with a group of amino acids (Ile32-Leu36-Ile40) in the neighboring TM1 helix, which resulted in an inefficient force transmission to the gate-constituting amino acids on TM1. This change also induced a slight tilting of TM1 towards the membrane plane and decreased the size of the channel pore at the gate, which seems to be the major mechanism for the inhibition of spontaneous opening of the double mutant channel. More importantly, the newly identified interaction between the TM2 (Phe78) and adjacent TM1 (Ile32-Leu36-Ile40) helices seems to be an essential force transmitting mechanism for the stretch-dependent activation of MscL given that substitution of any one of these four amino acids with Asn resulted in severe loss-of-function MscL as reported in our previous work.